2018
DOI: 10.1002/2017jd027504
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Mesoscale Simulations of the Coastal Flow Using Lidar Measurements

Abstract: The atmospheric flow in the coastal zone is investigated using lidar and mast measurements and model simulations. Novel dual‐Doppler scanning lidars were used to investigate the flow over a 7 km transect across the coast, and vertically profiling lidars were used to study the vertical wind profile at offshore and onshore positions. The Weather, Research and Forecasting model is set up in 12 different configurations using 2 planetary boundary layer schemes, 3 horizontal grid spacings and varied sources of land … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…An important aspect of the LSM, PBL, and SL sensitivity studies was the use of an alternative lookup table for the surface roughness length as a function of land use class. A custom NEWA lookup table was created since many values used in the WRF-distributed tables do not match the aerodynamic characteristics of European vegetation, especially over forests (Hahmann et al, 2015;Floors et al, 2018a). The new lookup table was created by polling wind energy resource assessment experts from the NEWA consortium.…”
Section: Effect Of Surface and Planetary Boundary Layer And Land Surfmentioning
confidence: 99%
See 2 more Smart Citations
“…An important aspect of the LSM, PBL, and SL sensitivity studies was the use of an alternative lookup table for the surface roughness length as a function of land use class. A custom NEWA lookup table was created since many values used in the WRF-distributed tables do not match the aerodynamic characteristics of European vegetation, especially over forests (Hahmann et al, 2015;Floors et al, 2018a). The new lookup table was created by polling wind energy resource assessment experts from the NEWA consortium.…”
Section: Effect Of Surface and Planetary Boundary Layer And Land Surfmentioning
confidence: 99%
“…Nowadays, wind atlases rely on the output from mesoscale model simulations, either sampling recurrent atmospheric states (e.g. Frank and Landberg, 1997;Pinard et al, 2005;Badger et al, 2014;Chávez-Arroyo et al, 2015) or by longterm simulations with Numerical Weather Prediction models (e.g. Tammelin et al, 2013;Nawri et al, 2014;Hahmann et al, 2015;Draxl et al, 2015;Wijnant et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERA5 resolves scales around 150 km. The use of structure functions and spectra from other numerical weather models has shown the effective model resolution to be about 6 times lower than the size of the grid cell (Frehlich and Sharman, 2008).…”
Section: Comparison Of Offshore Mean Wind Speed Maps At 100 M Heightmentioning
confidence: 99%
“…Mesoscale meteorological models are useful for offshore wind resource assessments [4]. However, some previous studies [5][6][7] have shown that offshore winds simulated by WRF near the coast, where offshore wind farms are likely to be located in Japan in the near future, are less accurate than those simulated over the open ocean. Therefore, the authors have recently focused on the horizontal wind speed gradient near the coast to improve the WRF offshore wind simulation in this location.…”
Section: Introductionmentioning
confidence: 99%